223k views
3 votes
Which of the following equations is equivalent to y + 3 = -4(x - 2)?

Which of the following equations is equivalent to y + 3 = -4(x - 2)?-example-1

1 Answer

2 votes

Answer:

D. y= -4x +5

Explanation:

  • The equation
    y+3=-4(x-2) can be transformed by doing some algebra.
  • If we solve the second term of the equation -4(x-2)= 8 - 4x, then we have
    y+3=8-4x
    (this is done by distributing the multiplication into the two terms: remember that the product of -4x(-2)=+8 because the product of two negative numbers is a possitive number).
  • Then, by subtracting both sides 3, we have
    y=5-4x. Rearranging terms in the right side, we have
    y=-4x+5, which is option D.
User Viilpe
by
6.3k points